Imagining fear: exploring the psychological impact of a culture of violence on women - Gordon, Sarah Frances (Department of Psychology, 2015)
Post-apartheid South Africa's current climate of patriarchy, social inequality and culture of violence has created a context in which violence against women is both prevalent and tolerated. Despite the extensive literature documenting the social problem of violence against women in South Africa not enough research has been conducted on how this culture of violence affects the identity construction of women. This qualitative, biographical-interpretive study explores how young women's lives and identities are transformed by living in this culture of violence against women in South Africa, more specifically the psychosocial impact this has on them. It draws on the theory of the psychosocial subject, allowing both a 'social' and 'individual' understanding of identity and the social problem of violence against women. Free-association, narrative interviews were conducted with 27 female, University of Cape Town (UCT) students, between the ages of 18 and 32. An interpretive analysis drawing on discourse analysis, narrative theory and psychoanalysis was used to analyse the interview texts. Findings revealed the overarching theme of the discourse of subordinate femininity, in which women are constructed as subordinate to men and their behaviour is constantly being regulated and disciplined. The study found that the discourse of subordinate femininity is reproduced through participants' narratives of family violence, fear and vulnerability and discourses of feminine self-regulation and transgression. The reproduction and resistance of the discourse of subordinate femininity is central to how these women construct their identity. Identifying the discourses of resistance embedded in participants' talk allows this study to represent both the suffering and resistance of these women, which is not commonly seen in literature surrounding violence against women, offering us a more comprehensive picture of how women construct their identity in a violent and volatile context, such as South Africa. The study also highlighted how the dissemination of discourses of subordinate femininity and feminine transgression contribute to the prevalence of violence against women in society because these discourses position men in a hierarchal corrective relationship to all women, and construct the violence perpetrated against women as a natural response to their transgression. Exploring these narratives and discourses allows us to see how all women, regardless of their experiences of victimisation, are affected by the prevalence of violence against women in society. This study addresses several gaps in the existing literature and is ground-breaking in terms of its unique subject matter, theoretical contributions, methodological approach and social significance to the South African context. It represents an original contribution to the field and is part of an effort to raise consciousness around violence against women and its impact on not only survivors, but all women.